Starch Hydrolysis and Vessel Occlusion Related to Wilt Symptoms in Olive Stems of Susceptible Cultivars Infected by Verticillium dahliae - Trapero, Carlos; Alcántara, Esteban; Jiménez, Jaime; Amaro-Ventura, María C.; Romero, Joaquín; Koopmann, Birger; Karlovsky, Petr; von Tiedemann, Andreas; Pérez-Rodríguez, Mario; López-Escudero, Francisco J. (Frontiers in Plant Science, 2018)
This study investigated starch content, amount of pathogen DNA and density of occluded vessels in healthy and Verticillium dahliae infected olive shoots and stems. Starch hydrolysis is considered a mechanism to refill xylem vessels that suffered cavitation by either, drought conditions or pathogen infections. The main objective of this work was to evaluate this mechanism in olive plants subjected to V. dahliae infection or to drought conditions, in order to know the importance of cavitation in the development of wilting symptoms. In initial experiments starch content in the shoots was studied in trees of cultivars differing in the level of resistance growing in fields naturally infested with V. dahliae. The starch content, esteemed by microscopic observation of stem transversal sections stained with lugol, decreased with the level of symptom severity. Results were confirmed in a new experiment developed with young plants of cultivars ‘Picual’ (highly susceptible), ‘Arbequina’ (moderately susceptible) and ‘Frantoio’ (resistant), growing in pots under greenhouse conditions, either inoculated or not with V. dahliae. In this experiment, the pathogen DNA content, quantified by real-time PCR, and the density of occluded vessels, recorded by microscopic observations of transversal sections stained with toluidine blue, were related to the symptoms severity caused by the pathogen. Finally, a drought experiment was established with young plants of the cultivar ‘Picual’ grown in pots under greenhouse conditions in order to compare the effects caused by water deficit with those caused by the pathogen infection. In both cases, results show that starch hydrolysis occurred, what indirectly evidence the importance of xylem cavitation in the development of the symptoms caused by V. dahliae but in the water stressed plants no vessel occlusion was detected.